O ressoar dos tambores do Congado: entre a tradição e a contemporaneidade: cotidiano, memórias, disputas (1955 2011) - Brasileiro, Jeremias (2012)
The main objective of my work is to understand the religious and cultural demonstration of Congado in Uberlândia under the perspective that goes through different forms of sociocultural reelaboration. This work shows the meanings which envolves some conflicts happened in the past between the Saint Benedict and Our Mother of Rosary Fraternity and some groups of Congado that had and still have various forms of disputes. These disputes come from the cultural living facts and are showm through images, testimonies and diverging memories. J also present some aspects in the production of discourses through oral testeimonies concerning to the transformation that occurs nowadays and how these questions and the tradition that gives sense to this practice are perceived by the different characters. Finally J reinforce some kinds of socio-cultural productions by the groups of Congado during many months of the year that demonstrates that the participants or congadeiros have an active cultural life in the city not only at those forty days organizing the Congado party. The chronological period covers the disputes during Saint Benedict and Our Mother of Rosary party from the 1950 s until the present days. The methodological procedures includes the use of oral and documental sources of Saint Benedict and Our Mother of Rosary and the accounts collected by other people and imagetic recourses in a way that the sources are crossed to form the theoric and methodological sources of the investigation. Therefore, many authors were very important to support this work on Congado; among them are Le Goff, Roger Chartier, Raphael Samuel, Thompson, Carlo Ginzburg.